The variety of phosphor Ca2MgSi2O7:Eu2+ emission color affect white light LEDs - Van De, Pham; Nguyen Thi, My Hanh (Institute of Advanced Engineering and Science, 2025)
The conventional phosphor-converted white light emitting diode (WLED) suffers from several drawbacks relevant to heat generation and low rendered performance. Thus, using ultraviolet LEDs was introduced as a solution. It is essential to choose the phosphors with high stability that can activated under 350-410 nm to be compatible with the chips. Rare-earth-doped silicate phosphor is among the most reserched materials for solid-state light devices, thanks to its high stability and low-cost production. This work presents the Eu2+ -doped Ca2MgSi2O7 green phosphor to serve the pursuit of comprehensively enhancing the WLED performances. The f–d transitions and Eu2+ ions mixture take possession of two seperate cation spots in main grids with the help of two emission peaks, one at 465 nm and another at 520 nm. The composition of YAG:Ce3+ and Ca2MgSi2O7:Eu2+ phosphors, and a near-UV chip of 370 nm were utilized to compose WLEDs. Results show that by increasing the Ca2MgSi2O7:Eu2+ phosphor amount, the lumen output, correlated color homogeneity, and color rendering factors can be improved. The paper emphasizes the necessity for the optimal selection of the Ca2MgSi2O7:Eu2+ phosphor concentration, which would be about 10 wt%. The phosphors could be promising in making green-induced white luminous materials for white pc-LEDs with near UV-base.